Prinsip Bimbingan dan Konseling Islami dalam Kegiatan Pembinaan Mental di Sekolah Polisi Negara Kepolisian Daerah Sumatera Utara - Siti Asiyah; Saipul Achyar; Abdurrahman Abdurrahman (Intiqad: Jurnal Agama dan Pendidikan Islam, 2020)
The research was backed by researchers ' interest to examine the guiding principles of guidance and counseling in North Sumatera regional Police School. This research aims to find out how the role of guidance and counseling in Mental development activities in North Sumatera regional Police School. Mental view of students who are studying police schools in North Sumatera regional Police School. The method used in this research is qualitative in the narrative approaches, That is, the research procedure that produces the detailed data of the written or oral words of the observed behaviour. The research of guidance and counseling principles in North Sumatera regional Police School: First, the role of caregiver in the motivation of the state Police school students by applying the principles in guidance and counseling, so it is achieved a good and mental healthy learning. This can be seen from the student's success to complete the learning process at the state Police School. Secondly, students ' mental assessment is reviewed from the issue that students have restrictions and obligations. This is included in the final aspect of this diploma in: Academic values, physical value and the most important mental value of personality are mental values of personality.